Transition Within the Teaching Pedagogy: A Stochastic Opportunity to Engage Problem Solving Skill Through CODE - Vaithilingam, C.A. (Springer Science and Business Media Deutschland GmbH, 2022)
Engineering curriculum primarily relies on the execution of learning strategy in knowledge skill and psychomotor skill. The COVID19 scenario forces a rethinking stochastic approach needed to continue run the courses without compromising the outcomes as agreed and endorsed by the various stakeholders. This work proposes a way in which the engagement of students and curriculum can be approached in the future through a stochastic approach using design thinking strategy. CODE is a design thinking approach used in the alternative shift in running curriculum due to the shift in the full digital mode of operation due the closed down of physical institutions place of learning. The framework, the key components, and the tracking of the performance to align the set outcomes are presented. Analysis on a sample core module from the engineering specific with action plan strategy over a semester is presented with reflections and effectiveness through on the programme outcomes reflections. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.